2019
DOI: 10.3916/c59-2019-04
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents problematic mobile phone use, Fear of Missing Out and family communication

Abstract: This research analyzes the problematic use of mobile phone, the phenomenon of fear of missing Out (FoMO) and the communication between parents and children in students who attend secondary education in public and private centers of the regions of Canary Islands, Balearic Islands and Valencia. The research involved 569 students aged between 12 and 19 years. The instruments used were the «Mobil phone related experiences questionnaire», the Spanish adaptation of the «Fear of missing out questionnaire» and the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 31 publications
2
36
0
9
Order By: Relevance
“…Our study is limited due to it being cross-sectional and the instruments used may have been associated with the effect of social desirability. Therefore, longitudinal studies are required (Livingstone and Smith, 2014) possibly up to the university level, including, among others, gathering information on emotional management (Amendola et al, 2019), focusing on other behavioral addictions possibly associated with previous psychological problems (Echeburúa and de Corral, 2010;Cía, 2013), and to investigate family communication (Santana-Vega et al, 2019) that can provide more information to the clusters. Finally, research for the delimitation of behavioral addictions, especially in DSM-5, remains necessary to advance proper diagnosis and treatment (Grant et al, 2010;Cía, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Our study is limited due to it being cross-sectional and the instruments used may have been associated with the effect of social desirability. Therefore, longitudinal studies are required (Livingstone and Smith, 2014) possibly up to the university level, including, among others, gathering information on emotional management (Amendola et al, 2019), focusing on other behavioral addictions possibly associated with previous psychological problems (Echeburúa and de Corral, 2010;Cía, 2013), and to investigate family communication (Santana-Vega et al, 2019) that can provide more information to the clusters. Finally, research for the delimitation of behavioral addictions, especially in DSM-5, remains necessary to advance proper diagnosis and treatment (Grant et al, 2010;Cía, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The quantitative scope of these changes has been documented by Santana, Gómez and Feliciano [7] who reported that 92.4% of the population, aged between 10 and 15 years, had incorporated such changes into their daily life for communicative and academic purposes [4]. Within this phenomenon, an availability factor has been outlined, with the number of homes in Spain with access to the Internet in 2019 being higher than 91% (International Telecommunication Union).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, Internet access it fundamentally provided through mobile devices. Amongst these, telephones are the most commonly used [7]. Mobile phone use has expanded for a number of purposes, principally, those that are professional and communicative in nature [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The quantitative scope of these changes has been documented by Santana, Gómez and Feliciano [7] who reported that 92.4% of the population, aged between 10 and 15 years, had incorporated such changes into their daily life for communicative and academic purposes [4]. Within this phenomenon, an availability factor has been outlined, with the number of homes in Spain with access to the internet being higher than 80%.…”
Section: Introductionmentioning
confidence: 94%